Biologically inspired catalyst for electrochemical reduction of hazardous hexavalent chromium. Issue 42 (26th October 2020) - Aralekallu, Shambhulinga; Palanna, Manjunatha; Hadimani, Sowmyashree; Prabhu C. P., Keshavananda; Sajjan, Veeresh A.; Thotiyl, Musthafa Ottakam; Sannegowda, Lokesh Koodlur
Abstract : A schematic diagram of the electrochemical reduction of Cr(vi ) using a modified electrode. Abstract : An indirect electrochemical detoxification and detection platform has been demonstrated for toxic hexavalent chromium (Cr(vi )) based on the biologically important N-4 macrocycle. The research work describes a simple, green, low-cost and potential way for the synthesis of a new N-4 macrocyclic molecule and the molecule is characterized by various analytical and spectroscopic techniques like elemental analysis, TGA, FT-IR, UV-visible, mass spectrometry and NMR spectroscopies, and cyclic voltammetry. The synthesized molecule was explored for the electrochemical reduction of Cr(vi ) using both voltammetric and amperometric methods. Amperometric studies exhibited 50 to 2500 nM linear range and the detection limit and quantification limit are 18 and 50 nM, respectively. The common coexisting metal ions did not interfere with Cr(vi ) even in the presence of 40-fold excess interfering ions. The real sample analysis was carried out with the fabricated sensor and successfully quantified a recovery result (98–104%) of Cr(vi ) in water. This proposed sensor is helpful in the detection of chromium ions in drinking water and is capable of detecting Cr(vi ) in the limits set by the World Health Organization (WHO). In addition, this sensor satisfactorily demonstrated considerable stability and reproducibility.